Impact of overtime payments on employees performance - Denis Deo Ocitti (Uganda Christian university, 2026)
This study examined the impact of overtime payment on employee performance at Uganda College of Commerce (UCC) Pakwach, Northern Uganda. The research specifically investigated the influence of overtime payment on employee motivation, the relationship between overtime payment and job satisfaction, and its effect on overall employee performance. A cross-sectional research design was adopted, targeting the entire staff population of UCC Pakwach. Using Yamane’s (1967) formula, a sample of 25 respondents was selected through purposive and simple random sampling techniques. Direct data collected using standardized questionnaires and semi-structured interviews, supplemented by secondary sources. Findings revealed a moderate positive perception of overtime payment’s influence on motivation (mean =3.30) and job satisfaction (mean =3.24), with fairness of rates and transparency in calculation emerging as key weak areas. However, overtime payment had the strongest perceived effort on overall performance (mean =3.50), particularly to optimize work quality. (mean =3.68) and productivity (mean =3.50). Pearson correlation analysis showed a strong statistically significant positive relationship between overtime payment and employee Performance (r=0.812, p<0.01). The study concludes that timely, fair, and transparent overtime payment significantly enhances employee performance in public tertiary institutions, while delays, low rates, and lack of transparency act as demotivators. It is recommended that UCC Pakwach management reviews overtime rates for competitiveness, improves transparency in calculation, and ensuring prompt disbursement to sustain motivation, satisfaction, and productivity. The findings contribute to the limited literature on overtime compensation in Uganda’s public collages and provide insights for administrators and policymakers in the education sectors.
Undergraduate